The Effect Of Small Sided Games Training On Passing Accuracy In SSB Star Soccer Kuningan Players - Listanto, Virgiawan; Muhtarom, Didi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aimed to evaluate the impact of small sided games training on passing accuracy in 20 12-year-old football players from SSB Star Soccer Kuningan, selected using total sampling. Using a one-group pretest-posttest design, passing accuracy data were collected before and after a four-week small sided games intervention. The results showed a statistically significant improvement (p=0.013), with the average score increasing from 7.40 to 8.85. The prerequisite Shapiro-Wilk and Levene's tests confirmed the normality and homogeneity of the data. This research concluded that small sided games effectively improves passing accuracy and also hones cognitive abilities such as decision-making, thus being recommended as a primary training method for young players.